Strategies for Increasing Intrinsic Motivation of Students in the Tahfidz Program - Ummul Fadilah; Lailatul Fitriyah (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study aims to describe strategies for increasing intrinsic motivation of students in the Tahfidz program at the Kanjeng Sunan Kalijogo Islamic Boarding School, Probolinggo. Intrinsic motivation is an internal drive that grows from the students' personal awareness and willingness to memorize the Qur'an without relying on external factors such as rewards or punishments. This study uses a qualitative approach with a case study method. Data were obtained through observation, in-depth interviews, and documentation involving the boarding school supervisor, the tahfidz ustadz, and the students as the main informants. The results show that increasing intrinsic motivation of students is done through several main strategies, namely fostering the intention and understanding of the meaning of memorizing the Qur'an, creating a religious and conducive Islamic boarding school environment, strengthening warm interpersonal relationships between ustadz and students, habituating worship and structured spiritual routines, and implementing various memorization methods according to the students' characters. In addition, the example of the ustadz and emotional support given to students has been proven to be able to increase students' sense of comfort, enthusiasm, and love for the process of memorizing the Qur'an. These strategies foster more stable internal motivation, enabling students to maintain consistent memorization. This study concludes that students' intrinsic motivation can be enhanced through an integrated educational, spiritual, and psychological approach across all tahfidz program activities. The implications of this research demonstrate the importance of Islamic boarding schools (pesantren) in creating a sustainable development system to support students' successful memorization of the Quran